2007
DOI: 10.1097/inf.0b013e31805d01e3
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized Children With Respiratory Syncytial Virus Infection and Neuromuscular Impairment Face an Increased Risk of a Complicated Course

Abstract: This is the first prospective multicenter study confirming the hypothesis that children with clinically relevant NMI face an increased risk for severe RSV-disease. It seems reasonable to include NMI as a cofactor into the decision algorithm of passive immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 26 publications
4
72
2
6
Order By: Relevance
“…Table I gives details of the medical history and the clinical situation of the patients at the time of diagnosis in the group ventilated mechanically (Table I). According to the categories of the DSM RSV Paed study [Simon Wilkesmann et al, 2007], the following age distribution was found: newborns (4 weeks), n ¼ 1 (5%); 5 weeks to 5 months, n ¼ 10 (50%); 6-12 months, n ¼ 7 (35%); 13-24 months, n ¼ 1 (5%); and >24 months n ¼ 1 (5%). Forty percent (n ¼ 8) of all RSV infections in the group ventilated mechanically were acquired nosocomially.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table I gives details of the medical history and the clinical situation of the patients at the time of diagnosis in the group ventilated mechanically (Table I). According to the categories of the DSM RSV Paed study [Simon Wilkesmann et al, 2007], the following age distribution was found: newborns (4 weeks), n ¼ 1 (5%); 5 weeks to 5 months, n ¼ 10 (50%); 6-12 months, n ¼ 7 (35%); 13-24 months, n ¼ 1 (5%); and >24 months n ¼ 1 (5%). Forty percent (n ¼ 8) of all RSV infections in the group ventilated mechanically were acquired nosocomially.…”
Section: Resultsmentioning
confidence: 99%
“…This may increase the risk of gastroesophageal reflux and recurrent aspiration. -Other preexisting comorbidities, as congenital heart disease [Feltes et al, 2003;Thorburn et al, 2004] or severe neuromuscular impairment [Panitch, 2004;Wilkesmann et al, 2007] contribute to an adverse outcome of infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations